Aerobic and Anaerobic Speed Predicts 800-m Running Performance in Young Recreational Runners - Støren, Øyvind; Helgerud, Jan; Johansen, Jan-Michael; Gjerløw, Lars-Erik; Aamlid, Aanund; Støa, Eva Maria (Frontiers in Physiology, 2021)
The main aim was to investigate the impact of maximal aerobic speed (MAS), maximal anaerobic speed (MANS), and time to exhaustion (TTE) at 130% MAS, on 800 m running time performance (800TT). A second aim was to investigate the impact of anaerobic speed reserve (ASR), i.e., the relative difference between MAS and MANS, on TTE. A total of 22 healthy students classified as recreational runners participated in a cross-sectional study. They were tested for maximal oxygen consumption (VO2max), oxygen cost of running (CR), time performance at 100 m (100TT), time performance at 800 m (800TT) and TTE. MAS was calculated as VO2max  CR-1, and MANS as 100TT velocity. Both MAS and MANS correlated individually with 800TT (r = -0.74 and -0.67 respectively, p  0.01), and the product of MAS and MANS correlated strongly (r = -0.82, p  0.01) with 800TT. TTE did not correlate with 800TT. Both ASR and %MANS correlated strongly with TTE (r = 0.90 and -0.90 respectively, p  0.01). These results showed that 800TT was first and foremost dependent on MAS and MANS, and with no impact from TTE. It seemed that TTE was merely a product of each runner`s individual ASR. We suggest a simplified model of testing and training for 800TT, namely by focusing on VO2max, CR and short sprint velocity, i.e., MAS and MANS.